A minimally invasive abdominal and left thoracic approach as a palliative treatment for adenocarcinoma of the esophagogastric junction with severe stenosis: A case report. Issue 2 (26th June 2019) - Takeuchi, Yuta; Ebihara, Yuma; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Kurashima, Yo; Murakami, Soichi; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: We report a novel technique for combined laparoscopy and thoracoscopy for far‐advanced adenocarcinoma of the esophagogastric junction (AEG). A 56‐year‐old man presented with far‐advanced AEG, and an esophagogastroduodenoscopy revealed a type 2 lesion that encircled the esophagogastric junction. CT revealed stenosis of the esophagogastric junction, suspected invasion into the left side of the diaphragm, and lymph node metastases in the abdomen. We diagnosed Siewert type II AEG (cT4aN1M0, cStage IIIA) according to the Japanese Classification of Gastric Carcinoma, version 14. Laparoscopic and thoracoscopic proximal gastrectomy and lower esophagectomy with double‐tract reconstruction were performed as a palliative resection via a minimally invasive abdominal and left thoracic approach. However, localized peritoneal dissemination was detected. The patient was discharged with no postoperative morbidity. Hence, a minimally invasive abdominal and left thoracic approach provides good visualization, and it is safe for lower esophageal transection and intrathoracic anastomosis in the treatment of locally advanced AEG invading the surrounding tissues.